An Analytical Calculation Method for Displacement Criterion on Tunnel Surrounding Rock Mass Stability. (24th January 2022) - Zhang, Zhiqiang; Chen, Fangfang; He, Mingming; Wang, Hui
Abstract : Assessment on the stability of a tunnel surrounding rock mass is an important issue during designing and construction of the tunnel. There is still no good enough analytical method to calculate the displacement criterion on the stability of the tunnel surrounding rock mass due to its multifactors dominated. In this paper, an innovative method to achieve the assessment displacement criterion, based on elastoplastic theory, is formed by considering multifactors, such as the quality of surrounding rock mass, initial stress, tunnel size, and supporting system. The calculation formula in this method is deduced by taking into consideration of combination the displacement and plastic region of surrounding rock mass and the reinforcement zone by systemic bolt, based on the equilibrium in elastic region, plastic region, and border between elastic region and plastic region. Furthermore, the influence of critical factors on the displacement criterion, such as deformation property and strength property of surrounding rock mass, tunnel size, and tunnel overburden, is discussed to make it clear that how these factors affect the stability of the tunnel surrounding rock mass. The validity of the analytical calculation method is testified by the application in the Zipingpu tunnel engineering.